2019
DOI: 10.1111/sms.13425
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of elite athletes with different cardiovascular demand

Abstract: Intensive exercise of elite athletes can lead to physiological alterations in the cardiovascular system in response to increased stroke volume and blood pressure, known collectively as cardiovascular demand (CD). This study aimed to compare metabolic differences in elite athletes with high vs low/moderate CD and to reveal their underlying metabolic pathways as potential biomarker signatures for assessing health, performance, and recovery of elite athletes. Metabolic profiling of serum samples from 495 elite at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 52 publications
1
29
1
Order By: Relevance
“…These morphological adaptations are essentially triggered by metabolic, immune-inflammatory, and neuroendocrine modifications. In particular, strenuous training in endurance athletes significantly alters their metabolic profile characterized by enhanced steroid biosynthesis, fatty acid metabolism, oxidative stress, and energy homeostasis ( Al-Khelaifi et al, 2018 , 2019 ). These metabolic changes are strongly associated with physical training pattern and cardiovascular demand, therefore, offer an opportunity to assess athlete’s performance and their cardiovascular and musculoskeletal transformations ( Al-Khelaifi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These morphological adaptations are essentially triggered by metabolic, immune-inflammatory, and neuroendocrine modifications. In particular, strenuous training in endurance athletes significantly alters their metabolic profile characterized by enhanced steroid biosynthesis, fatty acid metabolism, oxidative stress, and energy homeostasis ( Al-Khelaifi et al, 2018 , 2019 ). These metabolic changes are strongly associated with physical training pattern and cardiovascular demand, therefore, offer an opportunity to assess athlete’s performance and their cardiovascular and musculoskeletal transformations ( Al-Khelaifi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These adaptations, however, might be associated with a greater risk of cardiovascular disease. Indeed, we have recently shown that endurance athletes with high cardiovascular demand (higher blood pressure and stroke volume) show metabolic signature consistent with higher risk of cardiovascular disease (Al-Khelaifi et al, 2019a). When investigating the expression quantitative trait loci (eQTLs) associated with rs1052373, a number of genes was identified including SPI1, MYBPC3, MADD, ACP2 and NR1H3 (Ray et al, 1990;Tang and Chu, 2002;Mannan et al, 2004;Wu et al, 2012;Carrier et al, 2015;Theofilopoulos and Arenas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics analysis has presented a novel tool to validate genomics data by providing an intermediate phenotype (metabolites) in association with the identified genetic variants (Kastenmuller et al, 2015;Tanaka et al, 2016). Pilot metabolomics studies have revealed differences in the metabolic signature of moderate and high endurance elite athletes, such as steroid biosynthesis, fatty acid metabolism, oxidative stress and energy-related molecular pathways (Al-Khelaifi et al, 2018, 2019a. Recently, a study investigating metabolic GWAS of elite athletes showed novel genetically influenced metabolites associated with athletic performance.…”
mentioning
confidence: 99%
“…Furthermore, we should take into account the fact that a modified metabolic profile could also be the result of specific training (e.g. high altitude training 136 ), specific food supplements, 131 metabolic illnesses, 42 authorized medication, and because athletes participating in different sports have different cardiovascular demands that determine different metabolic profiles 131,137,138 . This fact could mask the markers of effect of the PEDs identified in the research frame.…”
Section: A Metabolomics Approach For Hormone Screening?mentioning
confidence: 99%